Effect of 3-Hydroxyphthaloyl-β-Lactoglobulin on Vaginal Transmission of Simian Immunodeficiency Virus in Rhesus Monkeys - Wyand, Michael S. (American Society for Microbiology, 1999)
Heterosexual transmission of human immunodeficiency virus type 1 (HIV-1) is the major cause of the ongoing AIDS epidemic. Application of chemical barrier methods is expected to contribute to the worldwide control of this epidemic. Bovine β-lactoglobulin modified by 3-hydroxyphthalic anhydride (3-hydroxyphthaloyl-β-lactoglobulin [3HP-β-LG]) was shown to inhibit HIV-1, HIV-2, simian immunodeficiency virus (SIV), herpes simplex virus type 1 and 2, and Chlamydia trachomatis infection in vitro. Here, we show that 3HP-β-LG not formulated into any vehicle protected three of six rhesus monkeys against vaginal infection by SIV. Incorporation of the compound into an appropriate vehicle is expected to increase the degree of protection. 3HP-β-LG may be effective as a vaginal inhibitor of HIV-1 infection in humans.